Trajectory length of pitch vs. roll: Technique for assessment of postural stability - Patrik Kutílek; Vladimír Socha; Ondřej Čakrt; Jakub Schlenker; Lucia Bizovská (Palacký University Olomouc, 2015)
Background: Patients with disorders of nervous or musculoskeletal system often show instability of the body segments during the stance tasks. Traditionally, stabilometric platforms are used to measure body sway. However, these devices are expensive and do not allow the evaluation of the individual movements of body segments. At present, accelerometers or gyroscopes are used to measure the movements of the body segments. For these new motion capture (MoCap) systems, methods for quantitative evaluation of a body segment movement are being developed. Objective: The main objective of this paper is to describe a new method which would be suitable for quantifying postural stability and identifying differences in balance control using data recorded by an inexpensive 2-DoF gyroscope. Methods: Method based on total length of trajectory (TL) in a 2-D plot of angles was proposed for quantitative evaluation of the trunk and feet sway. The sway was measured during quiet stance of ten middle-aged patients (Pts) with degenerative cerebellar disorder and eleven young healthy subjects (HS) standing with eyes open (EO) on a firm surface (FiS) and eyes closed (EC) on a foam surface (FoS). Data were obtained using three gyroscopes (Xsens) to measure roll and pitch angular movements of the trunk, and left and right foot. The pitch versus roll plots of the trunk and feet were created and the trajectory lengths of the pitch vs. roll angle were calculated. Results: Although the results vary while measuring different segments of the body, the method showed significant differences between the two different groups. Significant differences between the HS and Pts were found in EO standing on a FiS for TLs of the trunk (p = .02) and TLs of the feet (p < .01). Similarly in EC standing on a FoS significant differences (p < .01) between groups were found for TLs of both the trunk and the feet (p < .01). Conclusions: It was found that the TL of pitch vs. roll is suitable for quantifying postural sway and identifying differences in balance control. The technique, based on the length of the pitch angle vs. roll angle trajectory can be used even where MoCap systems can only measure two sway angles which could extend the clinical information of the body sway.